Adsorption Kinetics, Isotherms, and Thermodynamics of Removal of Anionic Surfactant from Aqueous Solution Using Fly Ash - Siyal, A.A. (Springer Science and Business Media Deutschland GmbH, 2020)
Surfactants are organic compounds which can be used in several applications. However, they can contaminate world water resources causing detrimental effects to human beings, aquatic life, and animals. This paper investigates the adsorption kinetics, isotherms, and thermodynamic properties for the removal of an anionic surfactant, sodium dodecylbenzene sulfonate (SDBS), using fly ash. Characteristics of fly ash such as surface area and pore size analysis and the point of zero charge (PZC) were determined. The effects of parameters such as pH, surfactant concentration, and temperature and the adsorption kinetics, isotherms, and thermodynamic properties and adsorption mechanism were determined. Fly ash is a mesoporous material having surface area and pore size of 1.079Â m2/g and 9.813Â nm and PZC at pHÂ 6.58. pHÂ 2 and the temperature 25Â Â°C were optimum for adsorbing SDBS onto fly ash. The adsorption capacity and removal efficiency increased by increasing the concentration of SDBS from 100 to 2000Â mg/L, indicating that the increase of surfactant concentration could not saturate the surface of fly ash. The pseudo-second-order and the Langmuir isotherm models showed best fit to the adsorption data and the thermodynamic properties described adsorption as an exothermic, barrierless, non-spontaneous, and entropy-reducing reaction which is more feasible at a lower temperature of 25Â Â°C. This indicated that the adsorption occurs by both physisorption and chemisorption with monolayer coverage of SDBS on the surface of fly ash. SDBS surfactant adsorbed onto fly ash mainly through electrostatic interactions between oppositely charged SDBS and fly ash. Â© 2020, Springer Nature Switzerland AG.